A theoretical review on the single-impurity electron spin resonance on surfaces. Issue 2 (May 2021) - Delgado, Fernando; Lorente, Nicolás
Abstract: The development of electron spin resonance (ESR) combined with scanning tunneling spectroscopy (STM) is undoubtedly one of the main experimental breakthroughs in surface science of the last decade thanks to joining the extraordinarily high energy resolution of ESR (nano-eV scale) with the single-atom spatial resolution of STM (sub-Ångström scale). While the experimental results have significantly grown with the number of groups that have succeeded in implementing the technique, the physical mechanism behind it is still unclear, with several different mechanisms proposed to explain it. Here, we start by revising the main characteristics of the experimental setups and observed features. Then, we review the main theoretical proposals, with both their strengths and weaknesses. One of our conclusions is that many of the proposed mechanisms share the same basic principles, the time-dependent electric field at the STM junction is modulating the coupling of the spin-polarized transport electrons with the local spin. This explains why these mechanims are essentially equivalent in a broad picture. We analyze the subtle differences between some of them and how they compare with the different experimental observations.